Nephroblastoma: treatment during 1970-3 and the effect on survival of inclusion in the first MRC trial. Issue 6190 (8th September 1979) - Lennox, E L; Stiller, C A; Jones, P H; Wilson, L M
Abstract : In 1970-3 313 children were diagnosed as having nephroblastoma in Great Britain. From the start of the first Medical Research Council nephroblastoma study in October 1970 until the end of 1973, 98 children (57% of all eligible children) were included in the trial. Of the 313 children, 288 (92%) had a nephrectomy, 248 (79%) received a course of radiotherapy, and 267 (85%) were given at least four days' chemotherapy. The three-year survival rate was 58%; the rate among children in the trial (77%) was significantly better than that among children who were eligible for the trial but not included (58%). Children who had nephrectomies at specialised children's and teaching hospitals had a higher survival rate than those treated elsewhere. All children with nephroblastoma should be treated according to well-defined protocols which take into account the age of the child and the stage of the tumour and include a full course of maintenance chemotherapy.